Multicentre feasibility of multiple-breath washout in preschool children with cystic fibrosis and other lung diseases. Issue 4 (26th October 2020) - Stahl, Mirjam; Joachim, Cornelia; Kirsch, Ines; Uselmann, Tatjana; Yu, Yin; Alfeis, Nadine; Berger, Christiane; Minso, Rebecca; Rudolf, Isa; Stolpe, Cornelia; Bovermann, Xenia; Liboschik, Lena; et al.
Background: Multiple-breath washout (MBW)-derived lung clearance index (LCI) detects early cystic fibrosis (CF) lung disease. LCI was used as an end-point in single- and multicentre settings at highly experienced MBW centres in preschool children. However, multicentre feasibility of MBW in children aged 2–6 years, including centres naïve to this technique, has not been determined systematically. Methods: Following central training, 91 standardised nitrogen MBW investigations were performed in 74 awake preschool children (15 controls, 46 with CF, and 13 with other lung diseases), mean age 4.6±0.9 years at investigation, using a commercially available device across five centres in Germany (three experienced, two naïve to the performance in awake preschool children) with central data analysis. Each MBW investigation consisted of several measurements. Results: Overall success rate of MBW investigations was 82.4% ranging from 70.6% to 94.1% across study sites. The number of measurements per investigation was significantly different between sites ranging from 3.7 to 6.2 (p<0.01), while the mean number of successful measurements per investigation was comparable with 2.1 (range, 1.9 to 2.5; p=0.46). In children with CF, the LCI was increased (median 8.2, range, 6.7–15.5) compared to controls (median 7.3, range 6.5–8.3; p<0.01), and comparable to children with other lung diseases (median 7.9, range, 6.6–13.9; p=0.95). Conclusion: This study demonstrates that multicentre MBW in awake preschool children is feasible, even in centres previously naïve, with central coordination to assure standardised training, quality control and supervision. Our results support the use of LCI as multicentre end-point in clinical trials in awake preschoolers with CF. MBW is feasible in awake preschool children with high success rates in a multicentre setting and LCI detects ventilation inhomogeneity in preschool children with CF. This supports LCI as an end-point in early intervention trials in preschool children with CF. https://bit.ly/3lD4wnj